SYNTHESIS OF ULTRASMALL CD0.3ZN0.7SENANOCRYSTALS VIA MECHANOCHEMICAL ROUTE - Bagudo, I. M.; Tanimu, A. (FUDMA Journal of Sciences, 2020)
Mechanical alloying through severe plastic deformation (SPD) was used to synthesize ultrasmall nanocrystals of (Cd0.3Zn0.7Se)with a diameter (d = 1.3 nm) after 20 hours milling time. A high-resolution electron microscope was (HRTEM) used to examine the mechanical deformation on the nanocrystals. The images reveal a bulk-like cluster structure without a distinctive regular shape. The atoms appear to be located entirely at the surface. The energy band-gap of the ultrasmall was determined to be 4.56 eV from UV-Vis absorption spectra.
Keywords: Mechanochemical synthesis; extremely small particles; optical property